KEPEMIMPINAN ROHANI SEBAGAI TELADAN DALAM PELAYANAN KEPADA SESAMA - Kasingku, Juwinner; Edwin Melky Lumingkewas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Leadership plays an essential role in guiding organizations and communities toward achieving shared goals. In the context of Christian ministry, leadership is not only related to managerial ability but also to spiritual character, integrity, and dependence on God. Effective spiritual leadership requires wisdom, faithfulness, integrity, and the ability to make responsible decisions while becoming a role model for others. This study aims to examine the concept of effective spiritual leadership based on biblical principles and the writings of Ellen G. White, and to explore its relevance for Christian leadership today. This research employs a qualitative approach using a literature study method. Various sources such as books, academic journals, and theological writings related to Christian leadership and Ellen G. White’s perspectives were collected and analyzed to identify key principles of spiritual leadership. The findings show that effective spiritual leadership is characterized by wisdom, faithfulness to God, integrity, humility, and dependence on divine guidance. A spiritual leader must seek God’s wisdom through His Word, demonstrate integrity in character and actions, and involve others in decision-making and ministry. Such leadership encourages growth, cooperation, and spiritual development within the community. In conclusion, effective Christian leadership is grounded in spiritual values and a close relationship with God. Leaders who practice wisdom, faithfulness, and integrity can positively influence others and faithfully serve as role models in Christian ministry.